Peirce's Triadic Analysis in the Script of "The Lord of the Rings: The Fellowship of The Ring" Film - Hamidah, Shelma Kamilia; Priyawan, Pepen; Abqoriyyah, Fourus Huznatul (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2024)
Using Charles Sander Peirce's theory, this study examines the object, representation, and interpretant in the screenplay for The Lord of the Rings: The Fellowship of the Ring. The research methodology employed in this study is qualitative research. Each of the triadic element is composed of three components. An object is denoted by an icon, which is a sign exhibiting a comparable appearance to its reference; an index, which signifies a connection between the representation and the object in terms of presence and occurrences; and a symbol, which is universally acknowledged through mutual agreement. Legisign, a sign in accordance with a general rule or code; qualisign, a sign perceived by quality; and sinsign, a sign based on actual shape or form, are all components of representation. The interpretant possesses rheme, which is a sign predicated on the interpreter's comprehension; dicent sign, which pertains to something that truly exists; argument, which comprises a justification for a given matter. The findings of this analysis indicate that the ring is of the utmost significance in the narrative of the film.